Projected 21st Century Wind‐Wave Climate of Bass Strait and South‐East Australia: Comparison of EC‐Earth3 and ACCESS‐CM2 Climate Model Forcing. Issue 4 (21st April 2023) - Liu, Jin; Meucci, Alberto; Young, Ian R.
Abstract: This study analyses the past and future wave climate of Bass Strait and south‐east Australia by comparing two high‐resolution regional wave climate models (RWCMs), respectively forced by the surface wind speed of EC‐Earth3 and ACCESS‐CM2 global circulation models (GCMs) under two emission scenarios (SSP1‐2.6 and SSP5‐8.5). The two RWCMs are verified against long‐term buoy and satellite observations as well as hindcast model data. The comparison with long‐term satellite altimeter observations shows good agreement between the long‐term model climate and the observations. Both RWCMs project a future increase in swell, approaching the coast of Tasmania and mainland Australia, generated from distant storms in the Southern Ocean. However, different projected wave height spatial distributions are found in the coastal regions, affected by local synoptic weather events and by the coarse resolution of the GCMs winds. We also show that the long‐term wave climate in the domain is impacted by the Southern Annular Mode. As low‐pressure systems are projected to move southward, especially in the SSP5‐8.5 scenario, the swells approaching south‐east Australia are projected to be longer and more energetic in the future. The combination of more energetic swell systems and a counterclockwise rotation in peak wave direction, projected by both RWCMs, may influence the coastal equilibrium, impacting critical coastal locations. Plain Language Summary: Two regional wave climate models (RWCMs) are used to study future wave conditions of Bass Strait and south‐east Australia by the end of the 21st century, under the Paris Agreement mid‐emission scenario (SSP1‐2.6) and a high‐emission scenario (SSP5‐8.5). The RWCMs are extensively validated against model and observational datasets, showing generally good agreement. The results indicate that Bass Strait and the coastal regions of eastern Victoria are dominated by local climate systems. However, both RWCMs show that swell approaching the domain will increase by the end of the 21st century. The long‐term wave climate variability in the domain is impacted by the poleward movement of low‐pressure systems in the Southern Hemisphere. Key Points: Two high‐resolution regional wave climate models (RWCMs), EC‐Earth3 and ACCESS‐CM2, are extensively validated against multiple datasets Both RWCMs project longer and more energetic swells approaching south‐east Australian coasts by the end of the 21st century The changes in the wave climate are directly correlated with a projected increasing trend in the Southern Annular Mode Index